Goat SNX29: mRNA expression, InDel and CNV detection, and their associations with litter size - Wang, Qian; Bi, Yi; Wang, Zhiying; Zhu, Haijing; Liu, Mei; Wu, Xianfeng; Pan, Chuanying (Frontiers in Veterinary Science, 2022)
The sorting nexin 29 (SNX29) gene, a member of the SNX family, is associated with material transport and lipid metabolism. Previous studies have shown that lipid metabolism affects reproductive function in animals. Thus, we hypothesized there is a correlation between the SNX29 gene and reproductive traits. To date, studies on the relationship between the SNX29 gene polymorphisms and reproductive traits are limited. Therefore, the purpose of this study was to examine the polymorphism in the SNX29 gene and its correlation with litter size. Herein, the mRNA expression levels of SNX29 were assayed in various goat tissues. Surprisingly, we found that SNX29 was highly expressed not only in the brain, but also in the corpus luteum, large and small follicles. This result led us to suggest that the SNX29 gene has a critical role in reproduction. We further detected potential polymorphisms in Shaanbei white cashmere (SBWC) goats, including insertion/deletion (InDel, n = 2057) and copy number variation (CNV, n = 1402), which were related to fertility. Two InDel loci (P1-Del-17bp, P2-Del-20bp) and four CNV loci (CNV1, CNV3, CNV4, CNV5) were polymorphic in the population of interest. The 17 bp deletion (n = 1004) and the 20 bp deletion (n = 1053) within the SNX29 gene were discovered to be significantly associated with litter size (P < 0.05), and individuals the ID genotype of P1-Del-17 bp (P < 0.05) and the DD genotype of P2-Del-20bp (P < 0.01) had larger litter size. Additionally, the four CNV loci had significant correlations with litter size (P < 0.01) in our detected population. In CNV5, individuals with the median genotype were superior compared to those with loss or gain genotype in term of litter size, and in other three CNVs showed better reproductive traits in the gain genotype. Briefly, these findings suggest that SNX29 could be used as a candidate gene for litter size in goat breeding through marker-assisted selection (MAS).